Users' satisfaction with the public dental service: the discovery of new patterns - Cristina Berger Fadel; Danielle Bordin; Celso Bilynkievycz dos Santos; Deborah Ribeiro Carvalho; Suzely Adas Saliba Moimaz (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2019)
Abstract Background Regarding to oral health, little has been advanced on how to improve quality within dental care. Objective The aim of this study was to identify the demographic factors affecting the satisfaction of users of the dental public service having the value of a strategic and high consistency methodology. Method The Data Mining was used to a secondary database, contemplating 91 features, segmental in 9 demographic factors, 17 facets, and 5 dominions. Descriptive statistics were extracted to a demographic data and the satisfaction of the users by facets and dominions, being discovered as from Decision Trees and Association Rules. Results the analysis of the results showed the relation between the demographic factor 'professional occupation' and satisfaction, in all of the dominions. The occupations of general assistant and home assistant with daily wage stood out in Association Rules to represent the lower level of satisfaction compared to the facets that were worse evaluated. Also, the factor 'health unit's name' showed relation with most of the investigated dominions. The difference between health units was even more evident through the Association Rule. Conclusion The Data Mining allowed to identify complementary relations to the user's perception about the public oral health services quality, constituting a safe tool to support the management of Brazilian public health and the basis of future plans.